Isolation and biochemical characterization of a gamma-type phospholipase A2 inhibitor from Crotalus durissus collilineatus snake serum - Cirilo Gimenes, Sarah Natalie; Ferreira, Francis Barbosa; Portella Silveira, Ana Carolina; Rodrigues, Renata Santos; Geraldo Yoneyama, Kelly Aparecida; Santos, Juliana Izabel dos [UNESP]; Mattos Fontes, Marcos Roberto de [UNESP]; Campos Brites, Vera Lucia de; Quagliatto Santos, Andre Luiz; Borges, Marcia Helena; Lopes, Daiana Silva; Rodrigues, Veridiana M. (Elsevier B.V., 2014)
In the present work, we describe the isolation and partial structural and biochemical characterization of the first phospholipase A(2) inhibitor (gamma PLI) from Crotalus durissus collilineatus (Cdc) snake serum. Initially, the Cdc serum was subjected to a Q-Sepharose ion exchange column, producing six peaks at 280 nm absorbance (Q1-Q6). Subsequently, Q4 fraction was submitted to affinity chromatography with immobilized PLA(2) BnSP-7, a step that resulted in two fractions (NHS-1 and NHS-2). The latter contained the inhibitor, denominated gamma CdcPLI. The molecular mass of gamma CdcPLI, determined by Matrix-Assisted Laser Desorption Ionization Time-of-Flight (MALDI-TOF), was 22,340 Da. Partial sequences obtained by Edman degradation and by mass spectrometry (MALDI-TOF/TOF), showed similarity, as expected, to other related inhibitors. Circular dichroism (CD) analysis showed the presence of approximately 22% alpha helices and 29% beta sheets in the protein secondary structure. Additionally, CD studies also indicated no significant changes in the secondary structure of gamma CdcPLI when it is complexed to BpPLA(2)-TXI. On the other hand, dynamic light scattering (DLS) assays showed a temperature-dependent oligomerization behavior for this inhibitor. Biochemical analyses showed gamma CdcPLI was able to inhibit the enzymatic, cytotoxic and myotoxic activities of PLA(2)s. Structural and functional studies performed on this inhibitor may elucidate the action mechanisms of PLA(2) inhibitors. In addition, we hope this study may contribute to investigating the potential use of these inhibitors for the treatment of snakebite or inflammatory diseases in which PLA(2)s may be involved. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Crotalus durissus collilineatus; Phospholipase A(2) inhibitors; Inhibitor gamma-type; Phospholipase A(2); Snake